Pendekatan Instruksional Adaptif dalam Pembelajaran Geografi sebagai Integrasi antara Teori dan Praktik Pedagogis di Sekolah Menengah Atas - Nefa Syafitri Fauzir; Kalara Kalara; Alya Marni; Balqist Salsabila Mukharromah; Rahmah Fadhillah; Ghina Asnah Aulia; Ade Irma (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Instructional approach adaptation is a learning strategy focused on adjusting teaching methods to students’ characteristics, needs, and psychological conditions. This study aims to describe the application of an adaptive instructional approach in Geography learning as an integration of theory and pedagogical practice at Senior High School. The research method employed was a qualitative case study through in-depth interviews, observation, and documentation with the Geography teacher. The findings indicate that the teacher implemented empathy-based and flexible teaching by utilizing digital media and projectbased methods to enhance students’ motivation and engagement. This approach effectively created an interactive and contextual learning process suited to students’ characteristics, representing a real integration between educational theory and classroom practice.